Cenozoic rifting and inversion of Beibuwan Basin and its linkage with the strike-slip movement along the Ailao Shan-Red River Shear Zone. Issue 20 (13th November 2022) - Cheng, Yanjun; Wu, Zhiping; Zhang, Jie; Liu, Yuqing; Wang, Zhengkai; Dai, Yining
ABSTRACT: The Cenozoic Beibuwan Basin is located along the eastern margin of the Ailao Shan Red River Shear Zone (ASRRSZ). The rifting and inversion processes of this basin provide important clues to the mechanism by which extrusion tectonics drive continental rifting and inversion development. However, the rifting and inversion of this basin remain ambiguous. Here, we employ seismic data, information about the time and displacement of faulting, syn-rift fault and isopach maps to analyse the Cenozoic rifting and inversion of Beibuwan Basin. Our results demonstrate that three stages of rifting and inversion occurred in this basin: (1) During the Palaeocene initial rifting, a series of NE-striking isolated half-grabens formed, which indicated that NW-SE extension dominated in this basin, and the southward slab-pull of Proto-South China Sea (SCS) was the likely cause of the extension. (2) During the Eocene rifting stage, besides significant motion on NE-striking faults, a small number of E-striking faults started to become active, which indicates that the extensional stress field shifted from NW-SE to N-S. (3) During the Oligocene rifting stage, the E-striking faults intensified, and controlled the distribution of the sediment depocentres, which implies that N-S extension dominated the deformation during this stage. The left-lateral strike-slip movement of the ASRRSZ and the slab-pull of the Proto-SCS are suggested to explain the extension stress field shift from NW-SE to N-S during the Eocene to Oligocene. (4) End-Oligocene, end-Miocene and end-Pliocene inversions have been recognized in this basin. The regional end-Oligocene inversion was stronger in the western area than the eastern area of the basin, which suggests that the compression caused by the left-lateral shearing of the ASRRSZ gradually decreased towards the east. In addition, the localized end-Miocene and end-Pliocene inversions occurred in the Haizhong sag.